Multiple papular lesions in a patient with HIV and/or AIDS and coinfected with hepatitis B virus: Amyloidosis - Hayati Demiraslan; Kemal Deniz; Mehmet Doganay (AOSIS, 2017)
Introduction: The most common form of systemic amyloidosis is amyloid A induced by a chronic inflammation. In HIV-infected patients, elevated serum amyloid A levels might be associated with chronic inflammation. Patient presentation: A 43-year-old male patient was admitted to hospital with a complaint of papular lesions around his eyes, existing for four months. The patient is receiving antiretroviral therapy. HIV RNA was undetectable, and the CD4 count was 770 cells/mm3. He suffered from a bladder carcinoma for four years. On examination, periocular, perioral and anogenital papules, papular lesions in the meatus of external auditory canal, and intranasal polyps were observed. Management: Microscopic examination of the biopsy material taken from the periocular lesion and then from perianal polyps revealed eosinophilic deposition, and stained positively by Congo red. Serum amyloid A level was negative. Antiretroviral therapy was continued. Conclusion: A rare form of amyloidosis in a patient with HIV and/or AIDS and coinfected with hepatitis B virus (HBV) was presented here with cutaneous and mucosal lesions.